Impact of information intervention on social distress; a randomised pilot study. (1st April 2011) - Ingleson, E J; Hector, C; Campbell, L; Bartlett, Y; Brown, J; Wright, P; Velikova, G
Abstract : Abstract: Introduction and aims: Unresolved social difficulties are prevalent in oncology patients, can impact on well-being and undermine ability to cope with the larger stressors of disease and treatment. Information may deal with psychosocial issues without over-burdening staff. A randomised pilot study investigated the impact of a specifically designed Support Services Information Pack (SSIP) on levels of social distress in routine practice. Methods: The SSIP was designed and evaluated. Adult patients receiving active treatment were randomised to intervention or control group. The Social Difficulties Inventory (SDI-21) assessed the severity of social difficulties at baseline and after the last of four review consultations. The intervention group received the SSIP prior to the second consultation. The sum of 16 of the SDI-21 items was used to provide an overall index of social distress (SD-16, range 0 to 44). All participants were interviewed on completion. Counts were taken of the number that used the SSIP. Analysis of covariance tests compared mean SD-16 scores. Results: Participants: 165 patients were approached, 88 consented and 75 completed the study. Complete SD-16 data was available for 70 patients. The SSIP was not extensively used; the majority of patients read it but took no action, but may use it in future (67%). The mean SD-16 scores were 8.53 for the intervention group (95% CI 7.1 to 9.9) and 8.25 for the control group (CI 6.7 to 9.8). Conclusion: During this pilot study the SSIP was not used. Timing of delivery of the intervention will be investigated in future trials.